Effect of Cobalt Phthalocyanine on the Chemical Polymerization of Aniline. Issue 19 (15th May 2020) - Andriianova, Anastasia N.; Abyalilova, Aigul R.; Biglova, Yulia N.; Mustafin, Akhat G.
Abstract: The synthesis of polyaniline (PANI) using organic metal complexes, for example, cobalt phthalocyanine ( CoPc ), is currently one of the promising approaches for PANI modification. Compounds of this kind favor the improvement of the properties of the target material and participate in the oxidative polymerization of aniline as catalysts. To fully understand the effect of CoPc on the synthesis and properties of PANI, the oxidative polymerization of aniline was monitored by measuring the open‐circuit potential (OCP) and pH, as well as by UV spectroscopy. Combining these techniques allows one to estimate the effect of the catalyst and assume the likely scheme of aniline oxidative polymerization with participation of the catalyst, as well as determine the extent of process acceleration. Abstract : The synthesis of polyaniline using organic metal complexes is currently one of the promising approaches for PANI modification. In this work was studied the effect of the catalyst and assume the likely scheme of aniline oxidative polymerization with participation of the catalyst.